TRANSMISSION AND REFLECTION CHARACTERISTICS OF A CLASS OF MODIFIED COPLANAR WAVEGUIDE STRUCTURES - Eldek, Abdelnasser A.; Elsherbeni, Atef Z.; Smith, Charles E. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
In this paper, several geometries of a class of grounded coplanar waveguide (GCPW) are investigated using the finite difference time domain (FDTD) method, and their losses are computed. A uniform grounded coplanar waveguide (GCPW) structure is used as a reference case for the other non-uniform geometries. First, this reference case is studied. For this case, four geometries are proposed to study the transmission and loss effect of replacing parts of the dielectric substrate with free space. Afterwards, two new geometries are simulated to study the effect of introducing a neck and a gap in the microstrip feeding line, with and without a bridge that connects the two parts of the microstrip feeding line separated with the gap. The effect of adding a PEC cap above the microstrip feeding line, and connecting the two side ground planes, is also studied. The conductor attenuation is studied for the basic GCPW geometry. The power losses are also calculated for the uniform geometries. The line impedance is calculated for all geometries at several points.